Tinjauan Hukum Administrasi Negara Terhadap Pelaksanaan Program Pendaftaran Tanah Sistematis Lengkap - Daming, Saharuddin; Ratnawaty, Latifah; Mustika, Desty Anggie; Husna, Mufidatul (Jurnal Legislasi Indonesia, 2023)
To realize legal certainty and guarantee land rights in order to create an orderly and maximally orderly land administration system towards a healthy and accountable land spatial structure, the government is promoting Complete Systematic Land Registration on a large scale. However, the problems that arise include: Is the Complete Systematic Land Registration a government policy that truly responds to the needs of the community? Is the implementation of the Complete Systematic Land Registration program carried out by the government in accordance with the order of state administrative law? The method used in this research is descriptive social legal which describes the operation of a complete systematic land registration law in the community. The conclusion shows that the Complete Systematic Land Registration is a government policy that truly responds to the needs of the community in registering their land. The implementation of the Complete Systematic Land Registration program carried out by the government is generally in accordance with the order of state administrative law, although there are still shortcomings.